Needle acupuncture for substance use disorders : a systematic review - Sullivan, Sean (Sean Grant) (RAND, 2015)
"RAND researchers conducted a systematic review that synthesized evidence from randomized controlled trials of needle acupuncture--used adjunctively or as monotherapy--to provide estimates of its efficacy and safety for treating adults diagnosed with alcohol, opioid, stimulant, or cannabis use disorder"--Publisher's description